2018
DOI: 10.1111/ajco.12997
|View full text |Cite
|
Sign up to set email alerts
|

Lymph nodes metastasis in cervical cancer: Incidences, risk factors, consequences and imaging evaluations

Abstract: Lymphatic metastasis was significantly related to the clinico pathologic characters and survival of cervical cancer. More sensitive preoperative evaluation is needed for predicting the LN metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
5
17
1
Order By: Relevance
“…For patients with early-stage cervical cancer, LN metastasis has been proven to be a critical risk factor related to survival 35. However, LN dissection may lead to lymphedema of the legs, nerve damage and lymphocyst formation in 14-32% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with early-stage cervical cancer, LN metastasis has been proven to be a critical risk factor related to survival 35. However, LN dissection may lead to lymphedema of the legs, nerve damage and lymphocyst formation in 14-32% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among these PRFs, PET/CT is the most commonly used for diagnosing pelvic lymph node metastasis, and the values are variable, with the sensitivity ranging from 8.3 to 82% in early uterine cervical cancer [9][10][11][12][13]. The reason for this inconsistent result may be that lymph node metastasis is not an independent behaviour but is affected by a variety of clinicopathological factors, including tumour differentiation, invasion depth of stroma, involvement of the parametrium, and so on [14]. Moreover, Benedetti-Panici reported that parametrial invasion was through direct extension in 37% of cases, by lymph node metastases in 59% and LVSI in 52% [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node (LN) metastasis is an important factor affecting survival rate and recurrence. LN metastasis seriously affects treatment and prognosis of cervical cancer (2). In 2018, the latest FIGO staging criteria reclassified LN metastases, indicating that all cases with LN metastasis are classified as stage IIIC (3).…”
Section: Introductionmentioning
confidence: 99%